Partial colocalization of NADPH-diaphorase and acetylcholinesterase positivity in spinal cord neurons - Kluchová, D; Schmidtová, K; Rybárová, S; Lovásová, K; Pomfy, M; Prosbová, T; Vatl'ak, A (Physiological research, 2000)
The freely diffusible radical, nitric oxide (NO), has been assumed to act as a retrograde signaling molecule that modulates transmitter release. Acetylcholine (ACh) is known to function as a typical neurotransmitter. In the present work we have examined the presence of both transmitters (NO and ACh) and their possible relations in the rabbit spinal cord. In our experiments we have used histochemical methods for the visualization of acetylcholinesterase (AChE) and NADPH diaphorase (NADPH-d) which label neurons that express nitric oxide synthase (NOS). Both histochemical methods were performed separately or together on the same sections of the thoracic spinal cord. NADPH-d positive dark blue stained neurons were seen mostly in superficial and deep layers of the dorsal horn, preganglionic autonomic neurons and pericentral area. The presence of AChE positive amber yellow neurons was confirmed mostly in motoneurons located in the ventral horns and in neurons of the pericentral and intermediate zone. Besides the above mentioned neurons, also double-labeled neurons were found which contained both the yellow and dark blue histochemical product. Their presence was confirmed in the intermediate zone and in the pericentral area. Thus, the co-existence of NADPH-d and AChE occurred in the location of interneurons. Our observations suggest that NO may play a role in the control of cholinergic neuronal activity and that NO can be involved in the modulation of synaptic transmission.
Keywords: Male; neurony; acetylcholinesterasa; Acetylcholinesterase; Rabbits; Animals; acetylcholin; oxid dusnatý; Nitric Oxide; histocytochemie; Neurons; mužské pohlaví; Female; Acetylcholine; mícha; ženské pohlaví; Spinal Cord; NADPH Dehydrogenase; zvířata; NADPH-dehydrogenasa; Histocytochemistry; králíci